Developing additional competition classes for athletes with intellectual impairments: Conceptual approach and efficacy of an ICF derived measure - Lemmey, S.; Burns, J.; Jones, F. (Journal of Sports Sciences, 2021)
The purpose of para sport classification systems is to minimize the impact of impairment on competition outcome. Currently, athletes with intellectual impairment (II) compete in one class, regardless of the extent of activity limitation resulting from their impairment. Consequently, athletes with II that cause relatively minor difficulty in sport have a competitive advantage over athletes who have intellectual impairments that cause more significant advantage. This research investigated the efficacy of a measure of health-related functional impairment, derived from the World Health Organization International Classification of Functioning, Disability, and Health (ICF), as a tool to classify athletes with intellectual impairments (II) into groups with impairments that cause similar activity limitation. The first study used a Delphi technique to identify the most relevant codes within the ICF from which a measure of impairment presence and severity was derived. The second study investigated whether the measure could discriminate between groups of II athletes organized into three competition groups, and whether these groups could be predicted by ICF score. The ICF-based questionnaire shows promise as a conceptual approach and as a tool in this context, but this is a preliminary step before establishing a sport-specific approach to classification.